Randomized clinical trial of Appendicitis Inflammatory Response score-based management of patients with suspected appendicitis. Issue 11 (21st July 2017) - Andersson, M; Kolodziej, B; Andersson, R E; Andersson, R E; Andersson, M; Eriksson, T; Ramsing, A; Westman, L; Björkman, J; Håkansson, H O; Lundström, T; Björkman, H; et al.
Abstract: Background: The role of imaging in the diagnosis of appendicitis is controversial. This prospective interventional study and nested randomized trial analysed the impact of implementing a risk stratification algorithm based on the Appendicitis Inflammatory Response (AIR) score, and compared routine imaging with selective imaging after clinical reassessment. Method: Patients presenting with suspicion of appendicitis between September 2009 and January 2012 from age 10 years were included at 21 emergency surgical centres and from age 5 years at three university paediatric centres. Registration of clinical characteristics, treatments and outcomes started during the baseline period. The AIR score-based algorithm was implemented during the intervention period. Intermediate-risk patients were randomized to routine imaging or selective imaging after clinical reassessment. Results: The baseline period included 1152 patients, and the intervention period 2639, of whom 1068 intermediate-risk patients were randomized. In low-risk patients, use of the AIR score-based algorithm resulted in less imaging (19·2 versus 34·5 per cent; P < 0·001), fewer admissions (29·5 versus 42·8 per cent; P < 0·001), and fewer negative explorations (1·6 versus 3·2 per cent; P = 0·030) and operations for non-perforated appendicitis (6·8 versus 9·7 per cent; P = 0·034). Intermediate-risk patients randomized to the imaging and observation groups had the same proportion of negative appendicectomies (6·4 versus 6·7 per cent respectively; P = 0·884), number of admissions, number of perforations and length of hospital stay, but routine imaging was associated with an increased proportion of patients treated for appendicitis (53·4 versus 46·3 per cent; P = 0·020). Conclusion: AIR score-based risk classification can safely reduce the use of diagnostic imaging and hospital admissions in patients with suspicion of appendicitis. Registration number: NCT00971438 (http://www.clinicaltrials.gov ). Abstract : Reduces imaging and admissions